PRINCIPLES OF FORMING A DEMONSTRATION OF LAND-ART WORKS IN A CLOSED SPACE - Кохан, Н. М.; Брижаченко, Н. С. (Art and Design, 2023)
The purpose of the work – to identify and formulate the principles for the formation of a demonstration of works of land art in a closed space. Methodology. General scientific and special research methods were used, in particular, typological analysis when grouping works of land art according to certain characteristics; historical and comparative analysis: used to identify the principles of the formation of the demonstration of land art works in a closed space; synthesis – during their formulation. Results. The search for sincerity in art in the second half of the 20th century led artists to the idea from exiting the closed space (museums and galleries, etc.) into the open space (natural environment). But the artists held the first exhibition of land art in the gallery (1968, New York, USA). This enabled the institutionalization of land art as a field of artistic activity, but also highlighted the paradoxical situation between the idea of the origin of this art and the place of its demonstration. The modern practice of land art also covers open and closed spaces. A comparison of the first works of land art at the exhibition (1968, New York, USA) and the works of modern Ukrainian artists on the example of the exhibition that was held as a result of the XXIV international land art symposium "Border Space" (2021) in the village of Mogrytsia of the Sumy region (Ukraine) made it possible to analyze the principles of the formation of the demonstration of land art works in a closed space, which were established in 1968 and their changes in the modern world. According to the typology of land art works presented in a closed space, three groups were formed: the artist creates his work of land art in the natural environment, fixes it in different ways (photo, video, etc.) and demonstrates it in a closed space; 2. A work of land art in a closed space is a semantic and visual continuation of a work of land art that has already been created in the natural environment, or the work exists in the process of its creation, or is a project (proposal); 3. A work of land art is formed in a closed space and can only exist and be displayed there. It was determined that photos and video documents presented in a closed space (according to the first principle) are not works of land art. Works of land art in a closed space include works formed in accordance with the second and third principles. Scientific novelty. For the first time, the principles of formation of the demonstration of works of land art in a closed space are singled out. The practical significance lies in the fact that these principles of forming the demonstration of works of land art in a closed space contribute to the creation of a more thoughtful work of land art and the formation of a modern competent exposition of the exhibition space.